Pathways to resilience: how drawings reveal pre-service teachers’ core narratives underpinning their future teacher-selves - Dinham, Judith; Chalk, Beryl; Beltman, Susan; Glass, C.; Nguyen, B. (2016)
For this study of teacher-identity, which is part of a larger research project on teacher resilience, preservice teachers were invited to draw “the kind of teacher you hope to become”. In this, our study recognises drawing as a semiotic system of meaning-making and communication. The drawings were examined in terms of the “stories” they told. Using an emergent design approach to the data, drawings were synthesised into categories that were distilled into theme clusters. A hermeneutic reading revealed the core identity narrative underpinning each teacher-identity story. This story was told in sociocultural terms, or constructed around functioning at work or couched in terms of personal validation and achievement. These core identity narratives signal what “matters” to preservice teachers’ sense of their teacher-selves. Since there is an observed correlation between teacher-identity and resilience, knowing what matters is a helpful basis for building resilience.